Some Metal Complexes of a New Carboxylate Derivative of L-Ascorbic Acid - Al-Najjar , Nada A.; Shanshal, Muthana A.; Mousa, Falih H. (Iraqi Journal of Science, 2022)
(4R)-2, 3-(2`-chloro-2`- carboxyl)-1, 3-dioxolano-4- (2- dimethyl –dioxolane -yl) ascorbic acid (HL), a derivative of L-ascorbic acid was prepared by the reaction of 5,6-O-isopropylidene–L-ascorbic acid with trichloroacetic acid in alkaline medium. Seven new metal ion complexes of this ligand (HL) were prepared through its direct reaction with the chlorides of Mn(II), Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II) ions respectively. The new ligand and its ion metal complexes were characterized applying elemental analyses,1H and 13C NMR, IR as well as UV-Visible spectra. Spectroscopic data showed that the ligand (C11H11O8Cl) was coordinated to the metal ions through the two oxygen atoms of the carboxyl group as abidentate ligand. Electrical conductivity and magnetic measurements were done at room temperature. Based on the obtained analytical data, the following molecular formulas for the prepared complexes are suggested; [M(L)2(H2O)2]. xH2O where x = 0 for Mn(II), Ni(II), Cu(II);x = 2 for Co(II); [M(L)Cl(H2O)3] for Zn(II) and Cd(II); and [Hg(L)ClH2O]. Octahedral geometry is suggested for all the complexes, except for the (Hg) complex which shows a tetrahedral geometry. Theoretical calculations of the molecular structure of the new ligand (HL) and its metal complexes were carried out too, applying the semi-empirical computation methods PM3 and PM6.The calculation results confirmed the suggested structures of all complexes.